6ER-009 Treatment patterns in multiple sclerosis with disease modifying drugs. (24th March 2020) - Rodrigues, M; Soares, A; Almeida, P; Armando, A; Vargas Gomes, M; Andreozzi, V; Félix, J
Abstract : Background and importance: Over the past few years, several drugs for the treatment of multiple sclerosis have become available. Current guidelines recommend treatment selection with disease modifying drugs (DMD) based on patient or provider preferences. Studies based on hospital pharmacies contribute to a better knowledge of drug utilisation patterns in a real world setting and are very important in informing healthcare decision making in multiple sclerosis treatment. Aim and objectives: We aimed to characterise time trends in the utilisation of DMD for multiple sclerosis, between 2012 and 2017. Material and methods: This was an observational cohort study based on hospital pharmacy claims data. All patients with multiple sclerosis, with at least one drug claim for any available DMD (interferon, fingolimod, dimethyl fumarate, glatiramer acetate, natalizumab or teriflunomide) between 2012 and 2017, in a general hospital, were eligible. Main outcomes included comparison of treatment patterns, treatment switches over time and oral drug uptake, between 2012 and 2017. Results: A total of 269 patients were included, with a mean age at first drug claim of 42.2 (SD 10.7) years. The sample included 13.0% naïve patients and the remaining had received treatment previously. In 2012, the majority of patients were receiving treatment exclusively with interferon (68.8%), glatiramer acetate (24.1%), natalizumab (4.0%) and fingolimod (1.0%); the remaining switched between treatments over 1 year. Despite more treatment options in 2017, interferon was still the most used (52.7%%), followed by glatiramer acetate (20.2%), teriflunomide (8.5%), natalizumab (6.9%), fingolimod (5.9%) and dimethyl fumarate (2.7%). Over the study period, 77.3% of patients never switched therapy, of these 53.2% remained on interferon, glatiramer acetate (18.6%) and natalizumab (4.5%). In 2012, almost all patients were receiving injectable DMD. During follow-up, oral DMD patient uptake rose from 0.6% in the third quarter of 2012 to 19.5% at the end of 2017. Conclusion and relevance: Unlike previous published studies, this cohort of patients did not show widespread adoption of oral DMD. This study also showed a low proportion of switches to new drugs, with the majority of patients still receiving treatment with interferon over a 6 year period. References and/or acknowledgements: No conflict of interest.